New Perspective of Elderly Care in Thailand 4.0 Era: Roles of Nursing Administrations - สุเมธสิทธิกุล อังคณา (Journal of The Royal Thai Army Nurses, 2018)
The global trend is moving towards the “aging century” which is the era of advanced technologies and an aging society. Thus, connecting elderly care and technology by application of current knowledge in real aging care are essential. The recent status of aging society causes fragility in health care problems related to this age group such as lack of caregivers. The rapidly increasing proportion of older adults results in a significant change in the population’s economic dependency. Further, aging people in Thailand 4.0 era have great experiences and available advanced healthcare and medications, reducing the mortality rate and improving quality of life and longevity. Thailand is also turning to the aging society with a rapid increase in the aging population. In 2015, approximately 11 out of 65.1 million people were aged 60 and older, accounting for 16% of the total population. The change in the population structure unavoidably impacts the economy and society. The potential consequences include physical limitations, and high risks of chronic diseases, morbidities, and dependency. Therefore, caring for elderlies in this era requires an adequate understanding of the current state of elderly care, environment and their lifestyles in reality. Additionally, positive thinking and a meaningful-life attitude are crucial to support older people to maintain peace of mind, mental security and live a happy life with proper life purposes.